2013
DOI: 10.1016/j.bbadis.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondria-targeted anti-oxidant MitoQ reduces aspects of mitochondrial fission in the 6-OHDA cell model of Parkinson's disease

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder for which available treatments provide symptom relief but do not stop disease progression. Mitochondria, and in particular mitochondrial dynamics, have been postulated as plausible pharmacological targets. Mitochondria-targeted antioxidants have been developed to prevent mitochondrial oxidative damage, and to alter the involvement of reactive oxygen species (ROS) in signaling pathways. In this study, we have dissected the effect of MitoQ, which is produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 45 publications
2
73
2
Order By: Relevance
“…Although our findings indicate that increased mitochondrial ROS production is at least partly attributed to mitochondrial fragmentation, prior studies have demonstrated that extrinsic ROS can cause mitochondrial fragmentation (13,38,45). Furthermore, ROS within CSE has been proposed as the representative mechanism for toxicity (49).…”
Section: L739contrasting
confidence: 40%
See 1 more Smart Citation
“…Although our findings indicate that increased mitochondrial ROS production is at least partly attributed to mitochondrial fragmentation, prior studies have demonstrated that extrinsic ROS can cause mitochondrial fragmentation (13,38,45). Furthermore, ROS within CSE has been proposed as the representative mechanism for toxicity (49).…”
Section: L739contrasting
confidence: 40%
“…chondrial fragmentation in the model of Parkinson's disease, an age-related neurodegenerative disorder (45). Hence, it is plausible that ROS in the CSE is responsible for modification of Drp1, resulting in activation and translocation to the mitochondria.…”
Section: L743mentioning
confidence: 99%
“…It is interesting that mitochondrial therapies have shown beneficial effects in different models of neurodegenerative pathologies, where mitochondrial dysfunction and apoptotic cell death are known to be involved, such as AD (Fossati, Ghiso & Rostagno, 2012b; Moreira, Carvalho, Zhu, Smith & Perry, 2010), Parkinson's disease (Solesio, Prime et al., 2013; Solesio, Saez‐Atienzar, Jordan & Galindo, 2012), and Huntington's disease (Solesio, Saez‐Atienzar, Jordan & Galindo, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…ROS are initially formed by the premature release of electrons from the ETC and the reduction of molecular oxygen to form the superoxide radical Á O 2 -which can damage mitochondrial components including mtDNA, respiratory chain complexes and lipid membranes [66,67]. Increases in mitochondrial fragmentation and ROS have been observed in many disease states including diabetes, ischaemia reperfusion injury (IRI), AD and PD [68][69][70][71][72]. In IRI, the production of ROS in the reperfusion stage results in fragmentation of the mitochondrial network [73].…”
Section: Drp1 Cardiolipin and Reactive Oxygen Speciesmentioning
confidence: 99%